THE STAGE OF SUPERVISION CAN DETERMINE THE QUALITY OF SERVICE AND MARKETING OF CLEAN WATER - Imas Sumiati; Nyi Raden Ruyani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Water is one of the most vital needs and absolutely needed by all living things,especially humans. In daily life, humans cannot be separated from their need forwater. For this reason, the provision of clean water is indispensable for drinkingwater needs. Data analysis techniques use formulas that are calculated using SPSSassistance. This study uses the theory of supervision, service quality and marketingtheory. Using secondary data, namely through documents such as organizationalstructure, vision and mission, realization data, etc. The research methods used byresearchers are quantitative methods and qualitative methods (mix-method) to be precise an explanatory mix-method design. The data collection techniques used wereprimary data by conducting interviews with the Service and Supervision Manager,non-participant observation, and distributing questionnaires to 30 respondents. Theresults showed that the Supervision Stages provided the same and unidirectionalassessment of service quality and clean water marketing. This means that if thesupervision has been carried out correctly and appropriately, the quality of serviceand marketing will also be good and vice versa if the supervision is not good thenthe quality of service and marketing will be not good. The obstacles faced inmonitoring the quality of service and marketing at the PDAM East Area RancaekekBandung Regency are poor facilities and infrastructure and areas that are stilldifficult to reach to market or distribute clean water due to small and few pipes.Efforts to overcome this are that the office needs to repair and improve facilities andinfrastructure to support services and carry out reservoirs for marketing clean waterso that service quality can be carried out quickly and precisely to the community